'Tommy Atkins' mango yield and photosynthesis under water deficit in semiarid region of Bahia - Marcelo R. dos Santos; Mauro A. Martinez; Sérgio L. R. Donato; Eugênio F. Coelho (Revista Brasileira de Engenharia Agrícola e Ambiental)
The aim of this study was to evaluate the 'Tommy Atkins' mango yield and photosynthesis in regulated deficit irrigation (RDI) in semiarid conditions of Bahia, Brazil. The experimental design was a randomized block with five treatments and six replications: T1, irrigation supplying 100% crop evapotranspiration (ETc) in phases: I (beginning of flowering to early fruit growth), II (start of expansion until early physiological maturity) and phase III (physiologically mature fruits); T2, RDI with 50% ETc in phase I; T3, RDI with 50% ETc in phase II; T4, RDI with 50% ETc in phase III; T5, No irrigation. The soil water deficit causes a reduction in photosynthesis. Mango yield in treatment 4 was approximately 5.5 and 2 times greater than in treatments 5 and 2, respectively. The use of RDI with 50% water depth reduction applied in the third phase of 'Tommy Atkins' mango fruit development was efficient. The use of RDI with 50% ETc in the third phase of fruit development provided the best yield of 'Tommy Atkins' mango for the 350 g weight class.